Development of a QR Code-Based Digital Attendance System to Improve the Efficiency of Student Attendance Management and Principal Decision-Making - Dewi Murni; Nurkolis Nurkolis; Muhtarom Muhtarom (Sakura Digital Nusantara, 2026)
Purpose: This study aimed to develop a QR Code-based digital attendance system to improve the efficiency of student attendance management and support data-driven decision-making by elementary school principals. Method: The study employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model over six months. Participants included the principal, teachers, administrative staff, students, and parents. The system was developed by integrating Google Forms, Google Sheets, Google Apps Script, and Canva. Expert validation was conducted by specialists in educational technology, information systems, and school management. Findings: The study produced a valid and practical digital attendance system that enables QR Code-based attendance recording, automatic data recapitulation, and real-time reporting. The system significantly reduced attendance processing time, improved data accuracy to above 95%, minimized recording errors, and provided timely attendance information. The generated data also supported principals in identifying attendance patterns, monitoring student discipline, and making evidence-based management decisions. Research Implications: The findings demonstrate that affordable digital technologies can enhance administrative efficiency and strengthen data-driven school management. The system offers a practical model for supporting school digitalization initiatives. Originality: This study contributes a QR Code-based attendance system specifically designed not only to improve attendance management but also to function as a decision-support tool for principals through real-time student attendance analytics.